1988
DOI: 10.1182/blood.v72.5.1456.1456
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic activity of recombinant human granulocyte colony- stimulating factor

Abstract: Recombinant human granulocyte colony-stimulating factor (rhG-CSF) induced migration across polycarbonate filters of human polymorphonuclear leukocytes (PMN). rhG-CSF was active in inducing PMN migration at concentrations greater than or equal to 10 to 100 U/mL (7 to 70 ng/mL). rhG-CSF did not contain appreciable levels of endotoxin contamination as assessed by Limulus amebocyte assay, and Polymixin B did not affect the chemotactic activity of rhG-CSF. A monoclonal anti-G- CSF antibody blocked the induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…In normal human neutrophils, fMLP increases chemotaxis activity and adhesive ability (Palmblad et al, 1981). rhG-CSF also stimulates human polymorphonuclear leukocyte (PMN) migration (Wang et al, 1988) and adhesion (Okada, Kawagishi & Kusaka, 1990). Although these chemoattractants increased chemotaxis and adhesion in our CNL case, the response rates was significantly lower than those in the control neutrophils as described previously (Kaplan et al, 1992).…”
Section: Discussionsupporting
confidence: 67%
“…In normal human neutrophils, fMLP increases chemotaxis activity and adhesive ability (Palmblad et al, 1981). rhG-CSF also stimulates human polymorphonuclear leukocyte (PMN) migration (Wang et al, 1988) and adhesion (Okada, Kawagishi & Kusaka, 1990). Although these chemoattractants increased chemotaxis and adhesion in our CNL case, the response rates was significantly lower than those in the control neutrophils as described previously (Kaplan et al, 1992).…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, the administration of rh G-CSF improved neutropenia and reduced leukocyte accumulation in the ileum and in the lung. The improvement in neutrophil count observed in SAO shocked rats treated with rh G-CSF does not seem to be the consequence of the in vitro and in vivo eects of the cytokine on proliferation and dierentation of neutrophilic lineage (Clark & Kamen, 1987;Wang et al, 1988); rh G-CSF was administered 75 min before the evaluation of peripheral neutrophil count and bone marrow myeloid precursor cells whereas it has been shown that an intravenous injection of the haematopoietic cytokine causes, after an initial neutropenia of between 5 and 30 min, neutrophilia signi®cantly evident only after 2 h and that peaks between 12 and 24 h (Ulich et al, 1988). In agreement with the kinetics of rh G-CSF haematopoietic eect, the recombinant hormone did not cause any increase in neutrophil count in sham rats or any stimulation of bone marrow myeloid precursor cells in either sham or shocked rats.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, GM-CSF augmented IL-8 production in 7 of 8 TAM preparations examined. Augmentation of chemokine production by in situ macrophages may act in concert with the attractant activity of GM-CSF itself (Wang et al, 1987) to amplify leukocyte recruitment.…”
Section: Discussionmentioning
confidence: 99%